HABITAT CHARACTERIZATION AND DIVERSITY ASSESSMENT OF MOSQUITOES FROM SELECTED COASTAL DISTRICTS OF KERALA, INDIA. - Uliyathel, SAJITH; MC, RATHY; CC, HARILAL (Recent Research in Science and Technology, 2016)
Abstract Vectors and host species in relation to environmental conditions are ensued in the effective transmission of many infectious diseases. Among the diverse array of vectors, mosquitoes stand at the top, spreading many devastating diseases to human beings such as Malaria, Dengue Fever, Chikungunya and Filariasis. Habitat heterogeneity and their physico-chemical attributes have vital influence on the diversity and distribution of such vectors. A better understanding of the mosquito diversity in relation to environmental characteristics thus assumes utmost significance in disease surveillance and control. Ponnani and Chavakkad municipalities of Malappuram and Thrissur Districts respectively, are known to be endemic to many mosquito borne diseases. Repeated reports of such diseases, especially filariasis, in recent years suggest the necessity to assess the diversity of mosquito vectors and the habitats they preferred. Â Species composition, relative abundance and distribution status of mosquitoes were evaluated after sampling of larvae from heterogeneous habitats in pre and post monsoon seasons. Mosquito larvae collected were reared to adults in the laboratory. Species level identification of all the collected mosquitoes were carried out following Christophers (1933) and Barraud (1934). Analysis of the water samples bearing larvae were also carried out for the assessment of physico-chemical characteristics. Â Larval density was higher in Chavakkad municipal area than Ponnani in both the seasons. Diversity of mosquito larvae during premonsoon season was higher (4 genera, 9 species) in Ponnani municipal area and lower (5 genera, 8 species) in Chavakkad. Similarly diversity during post monsoon season was higher (4 genera, 8 species) in Chavakkad municipal area and lower (4 genera, 7 species) in Ponnani.In both the seasons Culex was the most predominant genus with higher species diversity followed by Anopheles.Â The results have evidenced the existence of diverse groups of mosquito species with respect to seasons, which can act as potential carriers of so many infectious diseases such as Dengue, Chikungunya, Malaria and Filariasis in these coastal environments. Â Key Words: mosquitoes, diversity, Culex, Sewerage.